POLA KOMUNIKASI GURU DALAM MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS ISLAM INKLUSIF-MULTIKULTURAL - Nur Rizqiyah Al Karimah (Universitas Prof. Dr. Moestopo (Beragama), 2020)
The background of this study is that the learning model is not yet fully able to present an inclusive islamic paradigm, and a multicultural perspective for students, these are the limited space for differences of opinion between teachers and students, between each other of the student, so that the learning process is indoctrinative and educational focus is only on the achievement of the ability of ritual and tauhid beliefs with Islamic education teaching material that singular,that is right wrong and good bad. Data collection methods using interviews, observation, documentation studies and triangulation.The results showed inclusive islamic-multicultural islamic-based learning design including syllabus and lesson plans which included: material that contained normative texts and contained concrete cases in the society, the implementation based of the inclusive islamic-multicultural learning model educators are not stuck on one method, educators in attitude and speech are democratic and non-discriminatory, educators have a high level of concern for certain events, educators provide an understanding of the importance of deliberation in solving various problems, and this indicates that the learning process of Islamic Educational using inclusive islamic-multicultural based learning methods is using a multi-directional communication pattern. Beside, students become realize that they live in real situations that full of differences and make the educational paradigm that is not only to think, to do, and to be, but also to become an education paradigm to live together.